Synthesis of water-soluble star polymers based on cyclodextrins - Kotrchová, L; Etrych, T (Physiological research, 2018)
Novel star polymers based on the water-soluble N-(2-hydroxypropyl)methacrylamide (HPMA) copolymer and cyclodextrin were synthesized and the physico-chemical behavior of these precursors was studied. Semitelechelic HPMA copolymers were grafted onto the cyclodextrin core, thus forming star-like structure. Both prepared systems were designed as possible polymer carriers for the controlled release of cytostatic drugs, which after the drug release and degradation will be eliminated from the organism. Two synthesis approaches were used to obtain similar polymer carriers with different degradation rates. All the polymers were prepared by reversible addition-fragmentation chain-transfer polymerization, which guarantees low dispersity of the prepared systems.
Keywords: farmaceutická chemie; polymery; voda; Methacrylates; cyklodextriny; Polymers; Water; Chemistry, Pharmaceutical; Solubility; methakryláty; rozpustnost; Cyclodextrins